Genetic Determinism, Technology Optimism, and Race: Views of the American Public. Issue 1 (September 2015) - Hochschild, Jennifer; Sen, Maya
We begin with a typology of Americans' understanding of the links between genetic inheritance and racial or ethnic groups. The typology has two dimensions: one running from genetic determinism to social construction, and the other from technology optimism to technology pessimism. Construing each dimension as a dichotomy enables four distinct political perspectives on the possibilities for reducing racial inequality in the United States through genomics. We then use a new public opinion survey to analyze Americans' use of the typology. Survey respondents who perceive that some phenotypes are more prevalent in one group than another due to genetic factors are disproportionately technology optimists. Republicans and Democrats are equally likely to hold that set of views, as are self-identified blacks, whites, and Latinos. The article discusses the findings and speculates about alternative interpretations of the fact that partisanship and group identity do not differentiate Americans in their views of the links between genetic inheritance and racial inequality.